TWO NEW SPECIES OF DIAPHANOSOMA (SIDIDAE : CLADOCERA) FROM FRESHWATER BODIES OF NORTH ANDHRA, INDIA - RAO, L.M.; PADMAJA, G.; NAIDU, N.J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Two new species of Cladocera of the genus Diaphanosoma occurring in freshwater bodies of northern Andhra districts, India are described as Diaphanosoma siddharthii and D. chandramohanii.